The newcomer’s psychological contract breach and its change - Kim, KyungMin; Moon, HyoungKoo (Korean Journal of Industrial and Organizational Psychology, 2015)
This study has two primary aims: (1) to investigate the relationship between how the newcomer perceives employer promises psychological contract breach, and (2) to understand how these rates change over time. A total of 222 newcomers at major Korean companies were surveyed twice at a three-month interval. Results showed that both levels of perceived employer promise and psychological contract breach decreased over time as individuals accumulated real job experience. Also, the change in perceived employer promises was positively related to the change in breach perception. As their perceived employer promise level decreases over time, newcomers perceived fewer psychological contract breaches. This study provides evidence that a newcomer’s breach perception could result from overestimation of employer promise and that job experience plays a role in adjusting employer promise perception to an appropriate level, thereby lowering breach perception. These findings suggest that newcomers’ breach perception may be different from that of existing employees, due to incomplete initial understanding of employer promise, leading to increased frequency of breach perception. Practitioners may also benefit from education on new approaches for managing newcomers’ breach perception.